A rare complication of hypercoagulative state: Idiopathic left testicular infarct case - Onur, Rahmi; Tuygun, U?ur Oktay; Ozan, Tunç; Özercan, Reşat; Karaca, Ilgin; Da?li, Necati (My University, 2008)
Introduction: Testicular infarction in the absence of torsion is a rare idiopathic lesion and usually develops spontaneously. It may occasionally be associated with vasculitis, cholesterol emboli, malakoplakia, protein S or antithrombin III deficiency. We report a case of hemorrhagic testicular infarction developing in a 17-year-old male patient with no definitive etiology, despite receiving prophylactic anticoagulant therapy. Color Doppler sonography on testis demonstrated no blood flow and patient underwent scrotal exploration with subsequent orchidectomy. Histopathological examination revealed diffuse hemorrhagic infarction of the left testicle.
Ender bir hiperkoagülasyon yan etkisi: idiyopatik sol testiküler infarkt olgusu
Keywords: Coagulation; Infarct; Orchiectomy; Testis